Peran Financial Knowledge Dan Financial Attitude Terhadap Financial Management Behavior - Farichatul Izzah; Feri Dwi Riyanto (Universitas Hamzanwadi, 2022)
The purpose of this research is to know the role financial knowledge and financial attitude against financial management behavior . People's well-being can be experienced if the financial management system can be lived as well as possible. In reaching Financial Management Behavior needed Financial Knowledge and Financial Attitude the positive and the right one to apply directly. Without applying Financial Knowledge and Financial Attitude the good one , then it's hard for individuals to guarantee their lives in the term Long. This research is a type of empirical research by using qualitative descriptives that are trying to define, write, analyze and express what is observed with use method analysis concept/isi (text). Research the one done is researching every text contained in several journals and book. The data source in this writing is primary data in the form of related journals and secondary data in the form of books. Data the one had been collected next analyzed with use content analysis methods ( Content Analysis ) . The conclusion of this study is a danya Financial Knowledge then being able to master, analyze and manage financially to make something financial determination so that it has good behavior management. Financial attitude have a role against Behavior management i.e. d engan has insight to manage financially, but just a little financial insight is possessed so that it causes people to be less suitable in managing their finances. Financial Attitude will influence on Financial Management Behavior cause is one of the facades that influences financial attitudes accompanied by good financial management behavior.